Listening to Sutra-Chanting Reduces Bereavement Stress in Japan. Issue 2 (3rd April 2021) - Taniyama, Yozo; Becker, Carl; Takahashi, Hara; Tokumaru, Sadako; Suzuki, Iwayumi; Okui, Kazuki; Gohori, Josef; Imai, Yosuke; Morita, Takafumi
Abstract : Buddhist Chaplains chanting sutras after the Great East Japan Earthquake in 2011 often encountered survivors who felt that hearing sutra chanting itself ameliorated their bereavement grief. This research is the first experimental examination of the effects of sutra chanting on listeners' bereavement stress. Prior research demonstrates that sudden pet loss causes bereavement stress in students and that physiological stress can be noninvasively measured by salivary alpha-amylase. We asked Japanese college students to raise pet goldfish until they developed an attachment to them, then confiscated the fish, and told the students that they had to be killed. To compare the bereavement stress of groups listening and not listening to sutra chanting, we used psychological and salivary analyses. Perceived Stress Scale (PSS), Multidimensional Empathy Scale (MES), and State half of the State Trait Anxiety Inventory (STAI) psychological scales showed no statistically significant differences between sutra and control groups, but salivary analyses indicated measurable stress reduction in the sutra-listening group only. This pilot study tentatively confirmed the hypothesis that listening to Buddhist sutra chanting reduces Japanese bereavement stress. Further research is needed both to verify these stress-reduction effects and to determine whether such effects are primarily musical or cultural/spiritual.